Fish spread on open ground coated with cow dung - Mumbai Archive Project Team (Jio Institute, 2024)
The fish are spread evenly on the open ground, which is specially coated with cow dung. Cow dung contains antibacterial properties that help disinfect and sanitize surfaces. Coating floors with cow dung can help deter pests such as flies, mosquitoes, and ants, thereby reducing the risk of infestations and associated health hazards.